1998
DOI: 10.1002/(sici)1520-6394(1998)8:4<135::aid-da1>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety as a predictor of response to interpersonal psychotherapy for recurrent major depression: An exploratory investigation

Abstract: Major depression and anxiety frequently co-occur, but the implications for psychological treatments have rarely been studied. We examined predictors of acute response to interpersonal psychotherapy in 134 consecutively treated female outpatients with recurrent unipolar depression. Women who failed to remit with interpersonal psychotherapy alone experienced higher levels of somatic anxiety, were more likely to meet criteria for lifetime panic disorder, were more likely to meet criteria for nonendogenous or nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
0
21
3
Order By: Relevance
“…The subjects assigned to treatment as usual had more anxiety disorder diagnoses at baseline, a clinical characteristic associated with worse outcomes over time (37), which may account for observed differences in outcomes between groups. However, there were no differences in baseline levels of anxiety symptoms between groups as measured by the Beck Anxiety Inventory.…”
Section: Discussioncontrasting
confidence: 99%
“…The subjects assigned to treatment as usual had more anxiety disorder diagnoses at baseline, a clinical characteristic associated with worse outcomes over time (37), which may account for observed differences in outcomes between groups. However, there were no differences in baseline levels of anxiety symptoms between groups as measured by the Beck Anxiety Inventory.…”
Section: Discussioncontrasting
confidence: 99%
“…Among those who achieve remission with IPT alone, perhaps one characteristic of patient/therapist dyads is their ability (either inherent in the dyad or learned during acute treatment) to remain focused on interpersonal themes during the therapy sessions. This hypothesis is supported by analyses (26,27) demonstrating that subjects who did not do well in the acute phase of this trial tended to have higher levels of somatic anxiety symptoms, somatic complaints, and preoccupation with somatic changes-features likely to have interfered with their ability to focus on interpersonal themes during their therapy sessions. Thus, the ability to achieve stable remission with IPT alone may have selected the subpopulation uniquely able to remain focused on interpersonal themes and benefit from this specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As we reported earlier (26,27), subjects whose depression was complicated by panic-like symptoms or a panic spectrum disorder had a more problematic acute treatment course; however, these features are not captured by total scores on traditional measures of depression severity.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers also found that several factors were associated with good therapy outcome, including the ability to engage in more than one perspective and to take responsibility for actions, empathy for others, a desire to change, good communication skills, and a sense of cooperation and willingness to engage with the therapist. Feske et al (1998) examined predictors of outcome in 134 female patients with major depression, and found that those who did not improve experienced higher levels of anxiety and were also more likely to meet diagnostic criteria for panic disorder. In addition, they found that poor outcome was associated with greater vocational impairment, longer duration of episode, more severe illness, and surprisingly, lower levels of social impairment.…”
Section: The Development Of Interpersonal Psychotherapy (Ipt)mentioning
confidence: 77%